Synthesis of polypyrrole/tannin/cetyltrimethylammonium bromide nanocomposites for dopamine detection - Mohd Azli, Nor Farhana Waheeda (2018)
Polypyrrole-Tannin (PPy/TA) nanocomposite was prepared in the presence of cationic surfactant, cetyltrimethylammonium bromide (CTAB) using the chemical polymerization method. The resulting PPy/TA/CTAB nanocomposite was used to modify screen printed carbon electrode (SPCE) for developing a dopamine (DA) biosensor. The presence of TA was able to repel the interference molecules (AA and UA) in DA detection, while CTAB act as a soft-template in tailoring the nanostructure of PPy. The electrochemical properties of the modified electrode were studied via cyclic voltammetry (CV) and SPCE/PPy/TA/CTAB-modified electrode revealed a higher current response compared to modified electrode of SPCE/PPy and SPCE/PPy/TA. The results obtained from Electrochemical Impedance Spectroscopy (EIS) exhibited a lower value of charge transfer resistance (Rct) for the SPCE/PPy/TA/CTAB-modified electrode indicating an enhancement in the electron transfer rate. The Fourier-Transform Infrared (FTIR) spectra of nanocomposite displayed the typical characteristic peaks of TA and CTAB which are evidences of the incorporation of these components into PPy. Electron Microscopy (TEM) revealed a rod-like structure with a lumpy surface for PPy/TA/CTAB nanocomposite, justifying the highest current response for the modified electrode. Brunauer-Emmet-Teller (BET) measurement displayed a surface area of 23.5 m2/g for PPy/TA/CTAB nanocomposite. Response Surface Methodology (RSM) has been applied to optimize the selected parameters and conditions in order to maximize the biosensor’s performance and its sensitivity. Amperometry and Differential Pulse Voltammetry (DPV) analysis were employed for all electrochemical measurements and dopamine detection in two different ranges of 0.1–2 μM and 2–50 μM. The good adhesion of nanocomposite on the electrode surface, as well as the high surface area and porosity of the modified electrode, enhanced the diffusion of DA molecules inside the matrix. Amperometry analysis of the SPCE/PPy/TA/CTAB modified electrode displayed a good sensitivity of 0.039 μA (μM)−1 towards dopamine with the limit of detection (LOD) of 2.9×10−7 M. The modified biosensor also excludes the interfering species of ascorbic acid (AA) and uric acid (UA) which makes the sensor suitable for DA determination. This biosensor showed an acceptable reproducibility and repeatability with low relative standard deviations (RSD) of 4.8% and 4.4%, respectively. The current response remained about 81.5% of the original value after 21 days indicating an accepted stability over time.